2015
DOI: 10.5505/agri.2015.30085
|View full text |Cite
|
Sign up to set email alerts
|

Levels of pain and self-efficacy of individuals with osteoarthritis

Abstract: ÖzetAmaç: Bu araştırma; osteoartritli bireylerin ağrı ve öz-etkililik düzeylerini belirlemek amacıyla tanımlayıcı olarak yapıldı. Gereç ve Yöntem: Araştırma fizik tedavi ve rehabilitasyon kliniğinde yatan ve polikliniğe başvuran primer tanısı osteoartrit olan 83 bireyle yapıldı. Araştırmanın verileri, hasta tanıtım formu, vizüel analog skala (VAS), osteoartrit indeksi (Western Ontario and McMaster Universities Osteoarthritis Index-WOMAC) ve artritlerde öz-etkililik ölçeği kullanılarak toplandı. Verilerin değer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 20 publications
1
0
0
11
Order By: Relevance
“…Combining the results of univariate and multivariate analysis. We found a negative correlation between education and pain, which is consistent with some studies [36,37], suggesting that higher education level may accomplished by higher pain endurance. In this study, we also found that the prevalence of pain among rural residents is higher, which is consistent with the results of the study on farmers in Latin America and women in Tibet [38,39], subjects live in rural areas and, with lower education level seem to report their pain more easily.…”
Section: Discussionsupporting
confidence: 92%
“…Combining the results of univariate and multivariate analysis. We found a negative correlation between education and pain, which is consistent with some studies [36,37], suggesting that higher education level may accomplished by higher pain endurance. In this study, we also found that the prevalence of pain among rural residents is higher, which is consistent with the results of the study on farmers in Latin America and women in Tibet [38,39], subjects live in rural areas and, with lower education level seem to report their pain more easily.…”
Section: Discussionsupporting
confidence: 92%
“…La estrategia de búsqueda de estudios se presentó en forma de diagrama de flujo (Figura 1). Un total de 9 artículos (2 cohortes y 7 estudios transversales) se incluyeron en la revisión sistemática (Bieler et al, 2020;Degerstedt et al, 2020;Doğan et al, 2016;Harrison, 2004;Lazaridou et al, 2019;López-Bravo et al, 2021;Maly et al, 2007;Silva et al, 2020;Uckun et al, 2020). Las características de los artículos se muestran en la Tabla 1 y la Tabla 2.…”
Section: Resultsunclassified
“…La artrosis fue diagnosticada en la mayoría de los estudios (Bieler et al, 2020;Doğan et al, 2016;Harrison, 2004;Lazaridou et al, 2019;Maly et al, 2007;Uckun et al, 2020), gracias a los criterios de la American College of Rheumatology (ACR) (Wu et al, 2005). La ACR analiza la ubicación, el tamaño y la profundidad del daño del cartílago.…”
Section: Criterios De Diagnóstico De La Artrosisunclassified
See 2 more Smart Citations